Faktor-Faktor yang Berpengaruh Terhadap Lama Waktu Tunggu Rawat Jalan di Rumah Sakit Santa Elisabeth Batam Tahun 2016 - Silitonga, Timbul Mei (UI Scholars Hub, 2018)
Long waiting time of service in the Outpatient Unit describes the performance and quality of hospital’s service against its customers. The purpose of this research is to know the average length of outpatient waiting time as well as the factors associated with it, are reviewed through the approach of Malcolm Baldrige in health which includes: organization profile; leadership; strategic plan; focus on customers; measurement, analysis and management of knowledge; focusing on human resources; focus on process and outcomes. The research method used was the sequential explanatory, a mix methods between quantitative research that reinforced by qualitative research. Quantitative data collection by way of observation, calculation and recording patient waiting time. Qualitative data obtained through in-depth interviews are structured and do study related documents. The results showed that the average value of long outpatient waiting time is 66.58 minutes per patient means exceeding the standard minimum of service time, ≤ 60 minutes as defined by the Health Ministry of the Republic of Indonesia. The analysis results of the factors related to long waiting time outpatient showed that seven criteria of Malcolm Baldrige is so related to the average value of the long outpatient waiting time.